2022
DOI: 10.3171/2021.6.jns2122
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between social media utilization by academic neurosurgery departments and higher online patient ratings

Abstract: OBJECTIVE Patients increasingly utilize online physician review websites (PRWs) and social media to inform healthcare-related decisions. This provides neurosurgeons with opportunities for increased patient engagement. And despite the growing use of social media among neurosurgeons, the relationship between social media utilization and online reviews remains unknown. The goal of this study was to characterize the relationship between social media utilization and PRW ratings across academic neurosurgery departme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 32 publications
1
6
0
Order By: Relevance
“…Ensuring that patients have appropriate expectations and are properly educated about the risks of surgery may represent the best way to improve patient trust while simultaneously boosting review scores. 33-37…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ensuring that patients have appropriate expectations and are properly educated about the risks of surgery may represent the best way to improve patient trust while simultaneously boosting review scores. 33-37…”
Section: Discussionmentioning
confidence: 99%
“…Ensuring that patients have appropriate expectations and are properly educated about the risks of surgery may represent the best way to improve patient trust while simultaneously boosting review scores. [33][34][35][36][37] This study is not without limitations. Our study only included reviews listed on Yelp.com, Healthgrades.com, and Vitals.com.…”
Section: Figurementioning
confidence: 95%
“…Social media presence by institutions and neurosurgeons has been shown to positively influence patient reviews in neurosurgery. 26 , 27 In an increasingly digital age, it is imperative for practicing neurosurgeons and academic institutions to maintain a positive online presence. Given TikTok’s massive user base, it presents an opportune platform for physicians and institutions to amass interest in the field of neurosurgery and maintain a positive social media presence.…”
Section: Discussionmentioning
confidence: 99%
“…Lamano et al demonstrated that Twitter is second only to YouTube with respect to usage by academic neurosurgery departments, and is the social media platform most used by individual neurosurgeons. 1 , 5 …”
Section: Discussionmentioning
confidence: 99%
“… 1 , 4 Therefore, a reassessment of social media's relationship to traditional metrics of success in academic neurosurgery are warranted. 5 …”
Section: Introductionmentioning
confidence: 99%